Effect of using Agricultural Methods on the Growth and Yield of Three Types of Barley and Associated Weeds - Hayawi, Jasim Abdullah; Hameed, Raad Ahmed; Ahmed, Husham Abdul-Rahman; Faizy, Waad S. (American Journal of Biodiversity, 2025)
Research was conducted at the Rashidia Research Station with three main factors: first was three varieties of barley (Amal, Rehan and Samir), second was planting distances between lines (15, 30) cm, and third was seed rate (120, 160) kg. ha-1. Urea fertilizer was added at a rate of 240 kg. ha-1 In two batches, the research was carried out according to the global experiments system, in three sectors, and with a completely randomized block design. The data was analyzed using a computer and SAS program, with the Duncan multiple range test being employed for comparison means with different letters of the alphabet. The results were as follows: The variety Rehan outperformed the two varieties Samir and Amal are the most common species in terms of total weeds.m-2. Samir cultivar outperformed Rehan and Amal cultivars in terms of plant height, spike number m-2, and grain yield. Distance (30) cm is superior to distance (40) cm in the average characteristics of number of total weeds, and distance (15) cm is superior to distance (30) cm.. Study focuses on the average characteristics of plant height, number of spikes, and grain yield. Seed rate (120) kg.ha-1 was superior to the average (160) kg.ha-1. Average characteristic of total number of weeds is a crucial factor to consider, seed rate (160) kg.ha-1 was superior to average (120) kg.ha-1 in average. Average characteristic of total number of weeds is a crucial factor to consider. Interaction between barley variety Samir and the distance (30 cm) and rate (120) kg.ha-1 achieved highest yield, while lowest yield was when the interaction between variety Amal and distance (30 cm) and rate (120 kg.ha-1).